Studi Kinerja Ruas Jalan Jenderal Sudirman di Kota Pinrang Menggunakan Metode PKJI 2023 - Yusuf, Muh. Wahyu; Jasman, Jasman; Fadly, Imam (Sultra Civil Engineering Journal (SCiEJ), 2025)
Jenderal Sudirman Road, located in Pinrang Regency, is one of the main roads with high traffic intensity. The large traffic volume is influenced not only by daily community activities but also by the rapid development of shopping areas and its role as a primary access to several government offices. The growth of commercial and service centers has drawn significant vehicle movements, both private and public, leading to higher congestion. This condition requires a performance study to evaluate the road’s Level of Service (LOS), degree of saturation (DS), and capacity in accommodating increasing traffic flow. The objective of this study is to provide a clear picture of the existing condition of Jalan Jenderal Sudirman and serve as a foundation for effective urban traffic management and planning, with reference to the 2023 Indonesian Road Capacity Guidelines (PKJI). Data collection was conducted on Thursday, August 14, 2025 to represent a weekday and on Saturday, August 16, 2025 to represent weekend traffic conditions. The results indicate that congestion occurs mainly during peak hours, especially between 16:00 and 18:00 WITA. Analysis using PKJI 2023 recorded the road’s capacity at 2,632 PCU/hour under low side-barrier conditions. Peak traffic volume reached 2,426.07 PCU/hour, producing a degree of saturation of 0.92. This corresponds to LOS E, which reflects unstable flow, near-capacity conditions, and frequent reductions or halts in vehicle speed. Thus, Jalan Jenderal Sudirman can still accommodate current traffic demand but is operating under critical conditions, requiring immediate traffic management measures to handle congestion and anticipate future growth.